A Study of the Pre-service Secondary Teacher Education Programme in Jammu Province for Emerging Divergent Education Contexts: Perspective, Practices and Prospects - Sharma, Rajeev Ratan (INDIAN EDUCATIONAL REVIEW, 2016)
Education has a fundamental role to play in personal and social development. It cannot be considered as a magical formula, but it is definitely a principal mean available to foster a deeper and more harmonious form of human development and thereby would help technological and scientific changes which have accelerated the rate at which changes occur in the world today. In order to meet the ever growing demands of society one needs to put dynamic and ever evolving system of education. The changes have accelerated the rate at which changes occur in the world today. The task of building an enlightened, strong and prosperous nation rests on the shoulder of its children nurtured and developed with tenderness and care.